Equality of Opportunity and Human Capital Accumulation: Motivational Effect of a Nationwide Scholarship in Colombia (2018)
We study the ex-ante motivational effect of a nationwide merit and need-based scholarship in Colombia, which granted full scholarships to low-income students at high-quality universities. The results from a regression discontinuity design indicate that the opportunity to receive the scholarship significantly increased test scores at the national high school exit exam at the top of the distribution. At the 90th percentile of the distribution, eligibility for the scholarship reduced the socioeconomic achievement gap by 16 percent. In addition, we find that the eligibility to the  scholarship resulted in positive effects of on test scores of younger cohorts and increased post-secondary enrollment, even for the non-recipients of the scholarship. Our results highlight how opportunities for social mobility encourage human capital accumulation by low-income students, thus contributing to the break the persistence of poverty and inequality.